Nanocomposites for photonics and electronics applications - Kassab, Luciana Reyes Pires; Rangel-Rojo, Raul; Ribeiro, S. J. L. (Sidney J. L.) (Nanophotonics., 2019)
Nanocomposites for Photonic and Electronic Applications addresses a range of aspects of different nanocomposites and their possible applications to illustrate the techniques used to prepare and characterize them. In addition, the book discusses possible optical, electronic, biophotonic, photonic and renewable energy applications, presenting a panorama of current research in the field of nanostructures for photonic applications. This is an important reference source for academics and industry engineers who are looking to learn more about how nanocomposites can be used to make cheaper, more efficient products in the electronic and photonic fields.